Racialized disparities in pain and pain care among Belgian youth - Kissi, Ama; Carey, Sean; Debeer, Dries; Van Ryckeghem, Dimitri M. L.; Hirsh, Adam; Vervoort, Tine (Frontiers in Psychiatry, 2025)
IntroductionResearch highlights racialized inequities in pain and pain care, yet the experiences of youth–particularly in Europe–remain largely understudied. The current study addressed this gap by examining differences in perceived racialized discrimination in pain care and pain outcomes (i.e., pain intensity over the past two weeks and six months, pain frequency over the past six months, and pain tolerance) among Black/Brown and White youth in Belgium. Additionally, we explored whether perceived racialized discrimination mediated the relationship between racialized identity and pain outcomes.MethodsSeventy-six youth (52 girls, 17 boys, 2 non-binary individuals) aged 8-17 (Mage = 15.17; SDage = 2.48) completed a cold pressor task to assess pain tolerance. Participants also reported their experiences of racialized discrimination in pain care, their pain intensity over the past two weeks and six months, and their pain frequency over the past six months.ResultsResults indicated that Black/Brown youth reported greater perceived racialized discrimination in pain care and demonstrated lower pain tolerance than White youth. No significant group differences were observed for the other three pain outcomes. Perceived racialized discrimination in pain care only mediated the relationship between racialized identity and pain intensity over the past two weeks.DiscussionThese findings suggest that racialized disparities in pain and pain care exist among youth living in Belgium. However, given the relatively small sample size, the results should be interpreted with caution. Additional research on racialized disparities in pain and pain care among youth using larger and more diverse samples is warranted.